Caregiving Influenced by Gender and Spirituality - Turcic, Elizabeth Kreeft (Journal of religion, disability & health, 2004)
Current trends in American families point to the importance of sibling relationships as part of lasting family ties. In families where a child has a disability, siblings are often called upon to be caretakers of their sibling with a disability. Consistent with the research on the caretaking of elderly parents, females are more likely to become caretakers of members with disabilities due to gender role expectations. Such caretaking females face unique emotional and spiritual challenges as they cope with their unique role in the family. This paper will serve as an introduction to the explanation behind the caregiving role for sisters of siblings with disabilities and their consequent spiritual challenges and coping resources.